A Pain in the Flank. Issue 2 (11th March 2022) - Masood, Maryam; Panek, David; Butler-Wu, Susan; Spellberg, Brad
Abstract: Culture-negative endocarditis is rarely encountered and that caused by Bartonella quintana has been very rarely described. Virtually, all such cases in the literature have been related to human body louse exposure due to homelessness or living in refugee camps or similar environments. We describe a case of B. guintana endocarditis in a healthy adult with no exposure to body lice and no other risk factors. The patient also presented without fevers, which is also very uncommon. Rather, she presented with isolated flank pain due to a renal infarction, which led to an investigation for an endovascular source for emboli. The diagnosis was confirmed by a combination of serology and polymerase chain reaction from the excised valve. This case highlights the potentially atypical nature of culture-negative endocarditis and the power of multiplex polymerase chain reaction to make diagnoses that likely would not have been established in the past.